LITERATUR REVIEW: PERAN CENDAWAN NEMATOFAGUS TERHADAP NEMATODA PARASIT - Nurul Hikmah Erwin; Dewi Klarita Furtuna; Agnes Immanuela Toemon; Arif Rahman Jabal (Fakultas Kedokteran, Universitas Palangka Raya, 2022)
Nematofagus is a soil fungus that can reduce nematode worms and act as a biocontrol. This study aims to determine the type of nematofagus fungus that can reduce parasitic nematodes through a systematic review. The data sources in this study were obtained from google scholar, and NCBI. The results obtained were seven articles stating that the fungus Duddingtonia flagrans was able to kill nematode worms at stage L3, and three journals showed the fungus Pochonia Chlamydosporia could control nematode parasitic worm larvae. Next was the fungus Chysosporium spp, the fungus Trichoderma spp, and Purpureocillium lilacinum. Various types of nematofagus-reduced nematode parasites were Duddingtonia flagrans and Pochonia Chlamydosporia. Fungi have a role that is considered effective in reducing and controlling nematode parasites and can be used as biocontrol.